Monetary and Value Theory: A Critique of Lange and Patinkin - Archibald, G. C.; Lipsey, R. G. (Review of Economic Studies, 1958)
G. C. Archibald, R. G. Lipsey; Monetary and Value Theory: A Critique of Lange and Patinkin1, The Review of Economic Studies, Volume 26, Issue 1, 1 October